Pemahaman Konsep Matematis Peserta Didik pada Materi Bangun Ruang Sisi Datar Kubus Ditinjau Dari Gaya Belajar di Kelas VIII-8 UPT SMP Negeri 8 Medan - Teresia Br Pakpahan; Tia Basana Hutagalung; Tiara Habibi Swandi; Rosliana Siregar; Ratna Soraya (Departement of Mathematics Education, 2024)
This research aims to analyze students' ability to understand mathematical concepts in flat-sided spatial figures in terms of learning styles in class VIII-8 UPT SMP Negeri 8 Medan. This research method uses qualitative methods. Data collection techniques from questionnaire results in the form of a Google form which contains aspects of learning styles accompanied by indicators that must be answered and observations of learning activities. The written test used in this research was in the form of description questions regarding material on the flat side of a cube. This research was conducted in class VIII-8 UPT SMP Negeri 8 Medan which also served as the research subject. Based on the research results, most students in class VIII-8 UPT SMP Negeri 8 Medan for the 2023/2024 academic year have a visual learning style with a total of 82.43%, an auditory learning style 60.9% and a kinesthetic learning style 46.5%. Students have a tendency towards one of the visual, auditory or kinesthetic learning styles. Of the 31 students, it was found that 19 students had a tendency towards a visual learning style, 10 students had a tendency towards an auditory learning style and 2 students had a tendency towards a kinesthetic learning style. So it can be concluded overall that each student with a different learning style has a different understanding of mathematical concepts.